1984
DOI: 10.20506/rst.3.1.149
|View full text |Cite
|
Sign up to set email alerts
|

Further review of the epidemiology of rabies in Zambia (1975-1982)

Abstract: A review of rabies-positive cases between 1975 and 1982 showed that rabies occurred mainly in dogs. During this period a total of 1,384 cases were diagnosed, 1,076 (77.7%) of which were in dogs. During the same period, 280 cases occurred among farm animals, prin cipally in bovines (199 cases, 14.3%). The jackal was the most fre quently affected species among the wildlife population. Fourteen human cases were also confirmed at the laboratory during the same period. The role played by dogs and jackals in maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…This study confirms what has been previously observed that the domestic dog is the principal vector involved in the transmission and maintenance of rabies in Zambia (Hayles and Sachuk, 1976; Gaspar, 1977; Hussein et al., 1984) with an average of 2.93 (95% CI 2.59–3.29) positive cases per month for the period 1985–2004. This is consistent with observations made from other countries in sub‐Saharan Africa (Edelsten, 1995; Bingham, 2005).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study confirms what has been previously observed that the domestic dog is the principal vector involved in the transmission and maintenance of rabies in Zambia (Hayles and Sachuk, 1976; Gaspar, 1977; Hussein et al., 1984) with an average of 2.93 (95% CI 2.59–3.29) positive cases per month for the period 1985–2004. This is consistent with observations made from other countries in sub‐Saharan Africa (Edelsten, 1995; Bingham, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Hayles and Sachuk (1976) recorded a total of 1824 samples of which 702 were diagnosed positive giving an average of 140 positive cases per annum for the 5 years period 1970–1974. This was followed by a total of 3245 samples of which 1384 were rabies positive giving an average of 173 positive cases per annum for the period 1975–1982 (Hussein et al., 1984). The present study shows a reduction with an average of 53 positive cases per annum for the 20 years period 1985–2004.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rabies is endemic in both Zambia and Zimbabwe, with prevention attempts focusing on the strict use of vaccination and population control of dogs. Several wildlife carnivores such as jackals [2][3][4][5] and mongooses [6][7][8][9] have been implicated as reservoirs of rabies. However, in contrast to work in other regions, a study on the Selous mongoose (Paracynictis selousi) in Zambia ruled out the possibility of that carnivore being a wildlife reservoir of rabies in Zambia [10].…”
Section: Introductionmentioning
confidence: 99%